STUDY OF THE MINIMAL INHIBITED CONCENTRATION OF ISOLATED CULTURE OF BUGLEWEED (AJUGA GENEVENSIS L.) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The antibacterial activity of extractions from calli cultures of Ajuga genevensis L. was revealed. The character of antibacterial activity and the minimal inhibiting concentration of studied extractions towards E. coli was determined.
Keywords: antibacterial activity; extractions; $E.~coli$; minimal inhibiting concentration